2020
DOI: 10.1029/2019wr026720
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Bridge Piers on Scour at Downstream River Training Structures: Submerged Weir as an Example

Abstract: River training structures are conventionally used to improve river stability and ecological conditions and to protect the upstream instream infrastructures from scour and erosion. A submerged weir is a typical river training structure usually built downstream of bridges for grade control. Flow over the weir can cause local scour, destabilizing both the structure and the trained river reach. It is therefore important for safe design to estimate the scour accurately and understand the effects of an upstream brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Submerged weirs are training structures with the function of improving navigability. These structures are also built to improve river stability and ecological conditions and to protect the upstream in-stream infrastructures from scour and erosion [14]. Previous studies attempted to analyse the flow behaviour above such training structures using CFD.…”
Section: Submerged Weirs and Flow Behaviormentioning
confidence: 99%
“…Submerged weirs are training structures with the function of improving navigability. These structures are also built to improve river stability and ecological conditions and to protect the upstream in-stream infrastructures from scour and erosion [14]. Previous studies attempted to analyse the flow behaviour above such training structures using CFD.…”
Section: Submerged Weirs and Flow Behaviormentioning
confidence: 99%
“…The presence of distinctive 3D wake flows are often considered to be precursors for sedimentary bed morphology. Numerous studies have focused on the fundamental fluid-sediment interaction mechanisms for flow over finite square or circular cylinders [29,30]. McKenna Neuman conducted a series of experiments [10,31,32] on wind flow over short wall mounted obstacles of various geometries and concluded that local erosion patterns are correlated to the regions of coherent vortical structures.…”
Section: Introductionmentioning
confidence: 99%
“…The armor layer protects the riverbed and is important for the stability of the river channel. However, the flood control requirements can increase flow discharge and break the armor layer, inducing bed incision as well as scour at river banks or instream structures [1][2][3][4][5]. Stable armor layers commonly occur in poorly-sorted gravel-bed rivers when the imposed bed shear stress is less than the critical shear stress needed to initiate particle motion on the bed surface [6][7][8].…”
Section: Introductionmentioning
confidence: 99%